Killings of Police in U.S. Cities since 1980: An Examination of Environmental andPolitical Explanations - Kent, Stephanie L. (2010)
Most research on killings of police in urban areas attempted to link lethal violence against officers to the violence and disorder in the communities they work. Yet support for this relationship is inconsistent. Fewer studies considered whether local political arrangements affect killings of police. This study attempts to remedy this gap by using recent data to investigate the relationship between the political conditions of large U.S. cities and the number of homicides of police officers in the line of duty in the years 1980, 1990, and 2000. Negative binomial regression analyses suggest that racial income inequality and the size of the Black population are positively associated with killings of police but cities with African American mayors have less killings. Police killings of citizens are also positively related to officer killings. The results largely support political explanations and uncover time-contingent effects of segregation on violence against state representatives